Making Rural Services Work for the Poor and Women in Ethiopia - Mogues, Tewodaj; Petracco, Carly; Randriamamonjy, Josee (International Food Policy Research Institute, 2011)
Over the last several years, the Ethiopian government has committed substantial resources for the expansion of public services and infrastructure in rural areas. To what extent do these investments and services reach different social and economic groups in rural areas? This paper applies a public expenditure benefit incidence analysis of different public services in rural Ethiopia across gender and wealth groups. Among the results are findings that the gender gap in our study areas is substantial and that public works transfers are more progressive than direct support transfers.